Non-polar lipid components of human cerumen - Stránský, Karel; Valterová, Irena; Kofroňová, Edita; Urbanová, Klára; Zarevúcka, Marie; Wimmer, Zdeněk (Lipids, 2011)
Human cerumen was separated by column chromatography into the following groups of compounds: hydrocarbons, squalene, wax esters and cholesterol esters, triacylglycerols, free fatty acids, free fatty alcohols, monoacylglycerols, free cholesterol, free sterols, and free hydroxy acids. The groups of compounds obtained were examined in detail by gas chromatography and gas chromatography-mass spectrometry. In total, about one thousand compounds have been identified.
Keywords: Esters; lipidy; Gas Chromatography-Mass Spectrometry; estery; lidé; senioři; mužské pohlaví; Cerumen; Male; cerumen; chromatografie; Aged; plynová chromatografie s hmotnostně spektrometrickou detekcí; Chromatography; Lipids; Humans